Hubungan Sikap Siswa Terhadap Hasil Belajar Fisika di SMA N 10 Kota Jambi - Farradilla Handayani; Nabila Eka Wijaya; Ella Juli Astuti; Rimi Wandani; Tiara Sandari (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
This article was created with the aim of knowing the relationship between attitudes and learning outcomes of Class X Mathematics and Natural Sciences students at SMA Negeri 10 Jambi City. This type of research is descriptive quantitative research. Data collection techniques in this study used a questionnaire and test instrument. To measure attitudes using an attitude scale test based on content validation. The learning outcome test uses multiple choice questions with 25 items with material quantities and derivatives. Respondents in this study were students of class X MIPA 2 to X MIPA 4 at SMA Negeri 10 Jambi City. The sampling technique uses random sampling technique. The method used in this research is Descriptive Statistics. The data analysis requirements test used were the Normality Test, Homogeneity Test and Correlation Test. Based on the results of this study, it shows that there is a significant positive influence between the physics learning attitudes of students of class X MIPA 2 to X MIPA 4 on learning outcomes in the material quantities and derivatives.